Rekonstruksi Perlindungan Hukum terhadap Reputasi Institusi Pendidikan dalam Sistem Hukum Indonesia: Kajian Normatif terhadap Undang-Undang No. 1 tahun 2023 (KUHP) dan Undang – Undang ITE dalam Perspektif Hukum dan Pendidikan - Mulianto Mulianto; Stevanus Alpha; Ipan Morris Panggaribuan (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2026)
The development of information technology and the use of social media have increased the potential for defamation against various institutions, including educational institutions. The reputation of schools or educational institutions is an important social asset because it is directly related to public trust, institutional credibility, and the continuity of the educational process. However, the Indonesian legal system still places greater emphasis on protecting individual reputation than institutional reputation, creating a need to reexamine the legal position of educational institutions in responding to attacks on their good name. This study aims to analyze legal protection for the reputation of educational institutions within the Indonesian legal system and to formulate a more comprehensive reconstruction of legal protection that is relevant to the development of digital spaces. This research uses a normative legal method with statutory and conceptual approaches. Data sources consist of primary legal materials, including Law Number 1 of 2023 concerning the Criminal Code and the Electronic Information and Transactions Law, as well as secondary legal materials in the form of legal literature and educational theory. The results show that defamation provisions in the Criminal Code and the ITE Law have not explicitly provided adequate protection for the reputation of educational institutions. Therefore, legal protection reconstruction is needed through affirming educational institutions as legal subjects whose reputation deserves protection, strengthening reputation recovery mechanisms, and integrating educational ethics perspectives into legal regulation.